From improved water accounting to increased water productivity in the Fergana Valley - Karimov, Akmal A.; David, S.; Platonov, Alexander; Khamzina, A. (2011)
Facing competition for limited water resources with domestic, industrial, hydropower and environmental uses, agriculture has to adapt to produce more food with less water. This paper proposes to apply water accounting procedure to identify the scope for water productivity improvement. The Fergana Valley, a highly productive area within the upstream of the Syrdarya River Basin, was selected to examine the proposed procedure. Significant non-productive depletions of water as evaporation at 31-34% of the available water were identified in the Fergana Valley. There is also flow to sinks and pollution in the downstream at 1-5% of the gross inflow due to the changes of the river flow regime, its quantity and quality, caused by the return flow from the irrigated land and the winter hydropower releases from the upstream. Total non-productive depletions of water at 4,200-5,200 million m3 (Mm3) were identified in the form of evaporation, flows to sinks, and pollution. Proper water saving technologies to reduce non-productive depletions will improve water productivity in the Fergana Valley and increase water availability for the downstream water uses.